2014
DOI: 10.7863/ultra.33.11.2021
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of the Distal Iliopsoas Tendon Using a New Approach

Abstract: Sonography of the iliopsoas tendon plays an important role in the diagnosis and preoperative and postoperative management for the increasing number of patients under consideration for arthroscopically guided hip interventions such as iliopsoas tenotomy in a variety of conditions, including arthropathy, periarticular calcifications, and cam-type deformities of the femoral head. The ability to visualize the iliopsoas tendon pre-operatively can be helpful diagnostically in patients presenting with hip pain and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Balius et al 42 described the use of the ultrasonography in visualising the iliopsoas tendon preoperatively as well as postoperatively. They demonstrated that the FABER position increases the sonographic tendon exposure and is significantly superior to the classic method of examination (simple abduction and external rotation).…”
Section: Investigationsmentioning
confidence: 99%
“…Balius et al 42 described the use of the ultrasonography in visualising the iliopsoas tendon preoperatively as well as postoperatively. They demonstrated that the FABER position increases the sonographic tendon exposure and is significantly superior to the classic method of examination (simple abduction and external rotation).…”
Section: Investigationsmentioning
confidence: 99%
“…22 The iliopsoas tendon can be assessed to plan arthroscopically guided hip interventions, to treat periarticular calcifications, and to study cam-type deformities of the femoral head. 23 To better visualize the distal iliopsoas tendon complex in the longitudinal axis at its insertion on the lesser trochanter, it is useful to put the thigh in a flexed and externally rotated position 23 (►Fig. 4).…”
Section: Soft Tissuesmentioning
confidence: 99%
“…The lateral aspect of the iliacus attaches to the proximal femoral diaphysis as a direct muscle attachment [21]. Ultrasound evaluation of the distal aspect of the iliopsoas complex is improved with positioning the hip in flexion, abduction, and external rotation [22].…”
Section: Iliopsoas Complexmentioning
confidence: 99%